2015
DOI: 10.1002/iub.1381
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: miR‐212/132 downregulates SMAD2 expression to suppress the G1/S phase transition of the cell cycle and the epithelial to mesenchymal transition in cervical cancer cells

Abstract: MicroRNAs (miRNAs), a class of small noncoding RNAs that regulate target gene expression, play an important role in cancer initiation, progression, and metastasis. However, the role of many miRNAs in cervical cancer is not fully understood. In this study, we found that miR-212 and miR-132 from the same gene cluster are downregulated in human cervical cancer tissues when compared with adjacent noncancerous tissues. The overexpression of miR-212/132 not only led to a delay in the G1/S phase transition and repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 35 publications
6
53
0
Order By: Relevance
“…Smurf2, an ubiquitin ligase for Smads, also plays a vital role in the adjustment of TGF-β1/Smad signaling [40]. Smad was found to be negatively regulated by overexpression of miRNA [41]. As reflected in our study, miR-485 overexpression effectively inhibited the expression levels of Smurf2, α-SMA, TGF-β1 and Smad3.…”
Section: Discussionsupporting
confidence: 48%
“…Smurf2, an ubiquitin ligase for Smads, also plays a vital role in the adjustment of TGF-β1/Smad signaling [40]. Smad was found to be negatively regulated by overexpression of miRNA [41]. As reflected in our study, miR-485 overexpression effectively inhibited the expression levels of Smurf2, α-SMA, TGF-β1 and Smad3.…”
Section: Discussionsupporting
confidence: 48%
“…miR-132 is located on human chromosome 17p13.3, which is associated with various types of human cancer including osteosarcoma, gastric cancer (21), colorectal cancer (22), prostate cancer (23), breast cancer (24,25), hepatocellular carcinoma (26), pancreatic cancer (27,28) and glioma (29). Zhao et al (14) reported that the expression levels of miR-132 in CC tissues were lower compared with those in adjacent non-cancerous tissues, and it was revealed that miR-132 downregulated SMAD family member (SMAD)2 expression in order to suppress the G1/S phase transition of the cell cycle and the epithelial to mesenchymal transition (EMT) in CC cells. However, the mechanism resulting in the low expression of miR-132 in CC remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TSLP produced by CC cells promotes angiogenesis in an EOS-dependent and -independent manner (10,11). Watanabe et al (12) reported that high (14) reported that miR-132 expression was decreased in CC tissues compared with that in adjacent non-cancerous tissues. Transforming growth factor (TGF)-β is a multifunctional cytokine and may induce numerous important signaling pathways in several types of cancer cells (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…For the immunofluorescence assay, cells were incubated with anti-CADM2 antibody (1:100) and viewed using fluorescence microscopy. This assay was performed according to the method described by Zhao et al [48].…”
Section: Immunohistochemical Staining and Immunofluorescencementioning
confidence: 99%